Adherence to the dietary approaches to stop hypertension diet and risk of stroke: A meta-analysis of prospective studies. Issue 38 (September 2018) - Feng, Qinglin; Fan, Shibing; Wu, Yao; Zhou, Dailing; Zhao, Rui; Liu, Mingdong; Song, Yi
Abstract : Abstract: The Dietary Approaches to Stop Hypertension (DASH) diet has been shown to lower the risk of hypertension, but its role in the prevention of stroke remains in debate. We therefore conducted a meta-analysis to examine the association between DASH diet and incident stroke. A systematic database search in PubMed and Embase was performed to identify eligible prospective studies. The study-specific relative risks (RRs) and 95% confidence intervals (CIs) were pooled using random-effect meta-analysis. Dose–response relationship between DASH diet score and risk of stroke was also assessed. We included 12 prospective cohort studies comprising a total of 548, 632 participants, with follow-up duration ranging from 5.7 to 24 years. Compared with lower adherence, higher adherence to the DASH diet was related to a reduced risk of developing stroke (RR 0.88, 95% CI 0.83–0.93). Such a benefit of DASH diet seemed to be greater in the Asian than in the Western populations ( P for interaction = .037). Dose–response meta-analysis indicated a linear association of the DASH diet score with stroke ( P for nonlinearity = .411), and each 4-points increment in the score conferred a risk reduction of 4% (RR 0.96, 95% CI 0.94–0.97) in total stroke events. Our findings suggest that higher adherence to the DASH diet is associated with a decreased risk of stroke. Abstract : Supplemental Digital Content is available in the text